Claire Denis - Mayne, Judith (Book collections on Project MUSE., 2005)
Widely regarded as one of the most innovative and passionate filmmakers working in France today, Claire Denis has continued to make beautiful and challenging films since the 1988 release of her first feature, Chocolat. Judith Mayne's comprehensive study of these films traces Denis's career and discusses her major feature films in rich detail. Born in Paris but having grown up in Africa, Denis explores in her films the legacies of French colonialism and the complex relationships between sexuality, gender, and race. From the adult woman who observes her past as a child in Cameroon to the Lithuanian immigrant who arrives in Paris and watches a serial killer to the disgraced French Foreign Legionnaire attempting to make sense of his past, the subjects of Denis's films continually revisit themes of watching, bearing witness, and making contact, as well as displacement, masculinity, and the migratory subject.